Effects of Shooting with A Reduced Hoop Diameter Rim on Kinematics of a Basketball Free-Throw - Sioud, Rim; Amara, Sofiene; Gaied Chortane, Sabri; Khalifa, Riadh (Advances in Social Sciences Research Journal, 2023)
The purpose of this study was to determine the effects of a reduced rim diameter (diameter 0.30 m) upon the kinematics of basketball free-throws. Ten male basketball players (mean ± s; age 17.1 ± 0.4 years, height 1.85 ± 1.43 m, mass 79.0 ± 5.3 kg) performed 8 direct successful free throws; 4 when using a standard 0.45 m diameter rim, and 4 with an 0.3 m diameter rim. Ball release parameters and joint angles at ball release were determined for each participant. The smaller rim was associated with significant increases (p < 0.0001) in ball release angle, ball release velocity, ball release height and shoulder joint angle at release. The reduced diameter rim can be advocated as a tactic for developing a higher ball release angle when training the shooting technique of young basketball players; this is likely to maximize the probability of a successful free-throw when attempted into a standard rim.